DEVELOPMENT OF THE TEACHING MODULES OF SPEAKING 1 INTO THE TEXTBOOK SPEAKING 1 - Risa Risa; Sri Endah Kusmartini; Risnawati Risnawati; Darmaliana Darmaliana (HOLISTICS, 2018)
This study developed the teaching modules of Speaking 1 into the textbook of Speaking 1. It aimed to find out what kinds of materials and exercises that were suitable needed to improve the teaching and learning outcomes to be applied in the textbook of Speaking 1. Research and Development Methods that was developed by Gall and Gall (2003) were used to get the answer of the research question. Since the study had the limited time, the simplification steps that were developed by Emzir (2013) were chosen. All the steps were divided into two stages. This study found out that various kinds of topics, exercises, supporting aspects and strategies in every chapter gave good impacts in improving the students’ skill in speaking competence.